The Party the secret world of China's communist rulers - McGregor, Richard (New York Harper, 2010)
An eye-opening investigation into China's Communist Party and its integral role in the country's rise as a global superpower and rival of the United States.
Maps on lining papers.
Keywords: Zhongguo gong chan dang